Religious Da'wah in the Context of Religious Pluralism - Ilhami, Hamidi; Imadduddin, Imadduddin; Syadzali, Ahmad (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2023)
This article aims to discover how every religious adherent, individually or in groups, should carry out religious dakwah. In religious pluralism, religious communities can live in harmony and peace or at least avoid inter-religious conflict. The research method used is a descriptive qualitative approach with literature methods. The study results show that religious preaching in the context of religious pluralism lies in the pattern of interreligious relations, which are complementary and mutually improve one another so that all religions can collectively lead to a better life order.